In situ observations of wintertime low‐altitude clouds over the Southern Ocean. (17th April 2017) - Ahn, Eunmi; Huang, Yi; Chubb, Thomas H.; Baumgardner, Darrel; Isaac, Peter; de Hoog, Mark; Siems, Steven T.; Manton, Michael J.
Abstract : Cloud droplet concentration ( N d ), effective radius ( r eff ) and liquid water content (LWC) measured by a DMT CAPS and an SEA WCM‐2000 of wintertime low‐altitude clouds over the Southern Ocean (SO) are presented for 20 flights taken over 3 years (June–October, 2013–2015). Such clouds have been reported to have the lowest N d on record (10–40 cm −3 ) from the Southern Ocean Cloud Experiment (SOCEX I) field campaign in 1993. Of the total 20 357 one‐second records spent in cloud, 38.5% were found to contain ice crystals, primarily in mixed‐phase clouds (36.7%). Ice was observed at some point during 19 of the 20 missions. The droplet spectra and temperature range suggest these clouds were often ideal for the Hallett–Mossop ice multiplication process. The average N d and r eff for liquid clouds were 28 (±30) cm −3 and 12.5 (±2.9) µm, which are consistent with those from SOCEX I. Forty‐nine percent of all liquid cloud samples were observed to be drizzling with an average drizzle rate of 0.733 mm h −1 . As drizzle samples were commonly in the neighbourhood of mixed‐phase or non‐drizzling clouds, it was rare to observe solid patches of drizzle of greater than 10 s. On average, drizzling clouds had lower N d and greater r eff and LWC than those of non‐drizzling clouds. Distinct observations of non‐drizzling clouds with relatively high N d (∼89 cm −3 ), small r eff (∼8.5 µm) and low LWC (∼0.173 g kg −1 ) were noted for two flights. An initial examination of the local environment and synoptic meteorology for these flights failed to identify any particular forcing that may have led to these unique microphysical properties, although these were the only observations of closed mesoscale cellular convection. This research highlights that greater variability exists in the microphysics of wintertime clouds over the SO, when a wider range of synoptic meteorology is investigated.